2009
DOI: 10.1111/j.1365-2915.2008.00769.x
|View full text |Cite
|
Sign up to set email alerts
|

Enabling technologies to improve area‐wide integrated pest management programmes for the control of screwworms

Abstract: . The economic devastation caused in the past by the New World screwworm fly Cochliomyia hominivorax (Coquerel) (Diptera: Calliphoridae) to the livestock industry in the U.S.A., Mexico and the rest of Central America was staggering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 30 publications
(35 reference statements)
0
28
0
2
Order By: Relevance
“…For SIT effectiveness, to assure the mating between wild females and the released sterile insects is much more critical than only knowing the genotype of the insects (Robinson et al 2009). So far, there is not sufÞcient, unequivocal evidence through genetic analyses to contest the hypothesis that C. hominivorax is a single, panmitic species throughout both its historical and existing ranges.…”
Section: Discussionmentioning
confidence: 99%
“…For SIT effectiveness, to assure the mating between wild females and the released sterile insects is much more critical than only knowing the genotype of the insects (Robinson et al 2009). So far, there is not sufÞcient, unequivocal evidence through genetic analyses to contest the hypothesis that C. hominivorax is a single, panmitic species throughout both its historical and existing ranges.…”
Section: Discussionmentioning
confidence: 99%
“…have shown difficulties in the morphological differentiation of C. macellaria and C. hominivorax (unpublished data). Griffiths et al (2009), Torres and Azeredo-Espin (2009), Robinson et al (2009) and Lyra et al (2009) have reported the use of different molecular techniques and several modifications of the DNA isolation protocols for Cochliomyia spp. The principal changes were based on the type of sample (legs, abdomen and complete specimen) to be analyzed and focused to phenolchloroform or commercial kit methods, but the quantification and purity was not reported.…”
Section: Introductionmentioning
confidence: 99%
“…The annual losses caused by screwworm infestations in the United States, Mexico and Central America were significant; while in some Caribbean islands and South America it remains as a latent problem (Forero et al, 2007;Rodríguez et al, 2011). The programs based on the sterile insect technique eradicated the NWS caused by C. hominivorax from the southern United States, Mexico, Central America and some Caribbean islands (Robinson et al, 2009). For the period 2012-2021 the FAO has provided strategies for collecting information about the incidence of populations of screwworm and the impact of NWS on public health, in order to establish the eradication program in South America (FAO, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It produces severe cutaneous lesions in mammals, including domestic and wild animals and human beings (Guimarães & Papavero 1999). This fly was originally distributed throughout the southwestern USA and the Americas and has been eradicated from the USA, Mexico and part of Central America using the sterile insect technique (Galvin & Wyss 1996, Robinson et al 2009). In Brazil, this species is widespread and can be found in all states of the country.…”
Section: Introductionmentioning
confidence: 99%